Second tide's the charm - Blumberg, Chandra (Canary Street Press, 2024)
"At first glance, Hope Evans just landed the perfect job: spending the summer on a shark research boat. Except as every marine biologist knows, it's what's going on beneath the surface that counts, and Hope's new position comes with a big catch--the boat belongs to her ex-boyfriend, Adrian Hollis-Parker. For three years Hope's been treading water, staying away from anything that reminds her of their past. It's time to dive back into a job that could springboard her career--and maybe offer much-needed closure. Since their split, Adrian has risen to Internet fame as a shark expert with the launch of his YouTube channel to dispel myths and educate viewers about sharks. But success rings hollow without Hope"--